Longitudinal development of physical fitness in young football players: a Bayesian analysis - Berger, A. G.; Carvalho, H. M.; Cardoso, M. F. S.; Oliveira, J.; Delavald, V. A.; Pinto, R. S.; Leonardi, T. J. (Research Quarterly for Exercise and Sport, 2026)
This study investigated developmental changes in body size and physical fitness parameters in 76 young football players (12.22 ± 1.20 years; CI: 10.59-15.04 years) from a Brazilian club across 20 months. Players performed jumping, agility, intermittent endurance, and sprint tests. A Bayesian multilevel regression modeling approach was used to analyze performance relative to both chronological age (CA) and age at peak height velocity (PHV). The results indicate that stature and body mass increased non-linearly, while skinfold measurements remained stable across the period investigated. Physical fitness performance aligned more consistently with age at PHV than CA, and Bayesian models accounting for age at PHV exhibit greater homogeneity. These findings emphasize the importance of considering biological maturation when interpreting body size and performance changes in young football players. Considering both CA and age at PHV helps select more suitable training strategies throughout the long-term development process and enhances fairness while reducing the risk of overlooking potential talents in the athlete selection process.